2019
DOI: 10.24875/ric.18002843
|View full text |Cite
|
Sign up to set email alerts
|

Nutrigenomics as a Tool in the Prevention of Lipotoxicity: The Case of Soy Protein

Abstract: Obesity is associated with an increase of several metabolic disorders leading to the development of diseases such as type 2 diabetes and cardiovascular disease. This is due in part to the ectopic accumulation of triglycerides in organs that are non-adipose tissues, leading to lipotoxicity. Particularly, in the liver, the accumulation of lipids, mainly of triglycerides, leads to the formation of fatty liver. The accumulation of lipids in skeletal muscle and pancreas associates with insulin resistance and a decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 93 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…Therefore, the increase in serum triglyceride levels following d -allulose intake could have been caused in part by the decrease in the level of LPL, which leads to the inhibition of fatty acid uptake, and a subsequent reduction in serum triglyceride clearance. Soy protein has been reported not only to inhibit fatty acid biosynthesis through the reduction of the level expression of SREBP-1c and the production and release of very low-density lipoprotein (VLDL) but also to increase LPL activity. Sugano et al have shown that feeding on soy protein suppresses the secretion of triglycerides from the liver. Hence, considering such effects, co-administration of d -allulose and soy protein could have suppressed the higher serum triglyceride levels caused by d -allulose intake, which is supported by the decreased activities of hepatic enzymes related to fatty acid synthesis (FAS and G6PDH in Figure ) and the downregulated MTP mRNA expression, which is involved in VLDL secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the increase in serum triglyceride levels following d -allulose intake could have been caused in part by the decrease in the level of LPL, which leads to the inhibition of fatty acid uptake, and a subsequent reduction in serum triglyceride clearance. Soy protein has been reported not only to inhibit fatty acid biosynthesis through the reduction of the level expression of SREBP-1c and the production and release of very low-density lipoprotein (VLDL) but also to increase LPL activity. Sugano et al have shown that feeding on soy protein suppresses the secretion of triglycerides from the liver. Hence, considering such effects, co-administration of d -allulose and soy protein could have suppressed the higher serum triglyceride levels caused by d -allulose intake, which is supported by the decreased activities of hepatic enzymes related to fatty acid synthesis (FAS and G6PDH in Figure ) and the downregulated MTP mRNA expression, which is involved in VLDL secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Bioactive constituents, e.g . isoflavones, can activate AMPK and stimulate skeletal muscle uptake of glucose (Torres et al ., 2019). Thereby, this can maintain glucose balance for humans; likewise, isoflavones can reduce insulin resistance and improve insulin secretion (Clark et al ., 2018).…”
Section: Nutritional Properties and Physiological Functions Of Legume...mentioning
confidence: 99%
“…Consumption of a chronic high-fat diet (HFD) increases body weight and fat mass, which is a well-known powerful factor of obesity. Excess nutrients from dietary intake are stored in the form of lipid droplets in adipose tissue, but if the storage capacity of adipose tissue is exceeded, increased fat accumulation occurs in other tissues, including the liver, muscle, and heart [ 1 , 2 ]. Excessive lipid accumulation in non-adipose tissues can lead to cellular dysfunction, lipotoxicity, and cell death [ 3 ].…”
Section: Introductionmentioning
confidence: 99%